A Study on Software Project Tracking and Oversight Practices among Software Companies in Malaysia - Hock Ow, Siew (Malaysian Journal of Computer Science, 2005)
This paper reports on the outcomes of a survey conducted on software project tracking and oversight (SPTO) practices. The study was carried out from 3 May until 29 December 2004 (eight months). It included designing a questionnaire form to conduct the survey on the SPTO practices currently being adopted by the companies that develop software systems in Malaysia. The survey investigated all the five areas of the basic SPTO practices of the Software Engineering Institute’s Capability Maturity Model (SEI’s CMM). These include commitment to perform, ability to perform, activities performed, measurement and analysis, and verifying implementation. Data gathered for the survey were analysed using Statistical Package for Social Sciences (SPSS), Release 12.0.0 and MS Excel, to investigate the number and percentage of companies that practice the processes investigated. The survey findings show the practices that most companies are committed to perform, and the practice that is performed by the least number of the companies surveyed.